2016
DOI: 10.1007/s10943-015-0171-x
|View full text |Cite
|
Sign up to set email alerts
|

US Physicians’ Opinions about Distinctions between Withdrawing and Withholding Life-Sustaining Treatment

Abstract: Decisions to withhold or withdraw life-sustaining treatment (LST) precede the majority of ICU deaths. Although professional guidelines generally treat the two as ethically equivalent, evidence suggests withdrawing LST is often more psychologically difficult than withholding it. The aim of the experiment was to investigate whether physicians are more supportive of withholding LST than withdrawing it and to assess how physicians' opinions are shaped by their religious characteristics, specialty, and experience c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 37 publications
2
30
1
Order By: Relevance
“…In the literature, it has been shown that decisions of withholding are more frequent than withdrawing in ED as in our study . This could be explained by the fact that withdrawing life‐sustaining treatments was psychologically difficult and also more ethically problematic than withholding, as shown by Chung with US physicians . In a previous study, we demonstrated that these decisions were difficult for physicians who felt alone and overwhelmed during the decision‐making process and could be improved with systematic collegial reflection and specific training on end‐of‐life discussion …”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the literature, it has been shown that decisions of withholding are more frequent than withdrawing in ED as in our study . This could be explained by the fact that withdrawing life‐sustaining treatments was psychologically difficult and also more ethically problematic than withholding, as shown by Chung with US physicians . In a previous study, we demonstrated that these decisions were difficult for physicians who felt alone and overwhelmed during the decision‐making process and could be improved with systematic collegial reflection and specific training on end‐of‐life discussion …”
Section: Discussionmentioning
confidence: 73%
“…[2][3][4] This could be explained by the fact that withdrawing life-sustaining treatments was psychologically difficult and also more ethically problematic than withholding, as shown by Chung with US physicians. 19 In a previous study, we demonstrated that these decisions were difficult for physicians who felt alone and overwhelmed during the decisionmaking process and could be improved with systematic collegial reflection and specific training on end-of-life discussion. 20 Concerning reasons for making decisions of withholding or withdrawing life-sustaining treatments, we found that previous functional limitation and age were the most frequent criteria to justify limiting life-support therapies, whereas previous studies found that acute medical disorder was the principal criteria.…”
Section: Discussionmentioning
confidence: 88%
“…[1,2] Religion has earlier been shown to have tremendous effect on end-of-life decisions. [16,18,19,21,26] We have previously shown that physicians had less faith in God and considered religion to be less influential in ethical decisions in 2015 than they did previously. [22] Thus, it is not surprising that an appointment with a minister shifted the treatment decisions to life-prolonging modalities less often in 2015 than in 1999.…”
Section: Factors Associated With Physicians' Decisionsmentioning
confidence: 92%
“…This may be problematic for some bedside clinicians, particularly in the event that withdrawing mechanical ventilation is indicated during crisis standards of care. There are variations in physicians' perceptions of the ethical permissibility and psychological difficulty of withdrawing life support even under normal circumstances when the withdrawal is in-line with the patient's wishes for end of life care (Chung et al 2016). Unilateral decisions to withdraw life support are likely to be even less acceptable to these clinicians.…”
Section: Introductionmentioning
confidence: 99%